An Occupation-Based Approach to Management of Concussion: Guidelines for Practice - Christina Finn (Scholarworks @ WMU, 2019)
Concussion and the cumulative effects of repetitive head trauma have become a growing health concern both in the mainstream media and in the health care community. Although symptoms of concussion are not always outwardly visible, evidence suggests that post-concussion symptoms may interfere with an individual's ability to work, play, and participate in school. In the past, the recommendations following concussion emphasized a complete rest approach, whereas current approaches focus on a gradual engagement in functional activities shortly after the injury. Since current recommendations are focused on a gradual engagement in occupation and activity, occupational therapy may be a valuable service for individuals who have sustained concussions. However, despite the valuable role that occupational therapy may offer, there is limited literature supporting the role of occupational therapy in the management of concussion, and there are currently no clear guidelines for clinical practice. This paper will provide an overview of an occupation-based, client-centered framework for the management of concussion and specific guidelines for occupation-based assessments and interventions.